Taxonomy and phylogeny of crustose brown algae (Phaeophyceae) from Malaysia and Lombok Island, Indonesia / Poong Sze Wan - Poong, Sze Wan (2014)

(untitled)
Studies on crustose brown algae are relatively few despite a long history of studies conducted since the 1800s, with temperate species forming the bulk of these studies. There is a need for more focus on crustose brown algae particularly in the tropics as they are generally different from those in the temperate regions. These algae received little attention due to their simple appearance (brownish-black spots on rocks) and lack of apparent economic value despite some being the dominant flora of certain habitats. Taxonomic confusion arising from morphological simplicity largely dependent on the reproductive structures and overlap in morpho-anatomical features among species necessitates the use of molecular approach. This study aims to enhance our understanding of the taxonomy and phylogeny of these understudied algae in Malaysia and Lombok Island by combining morpho-anatomical observations and molecular sequence data [plastid rubisco large subunit (rbcL) and partial mitochondrial cytochrome c oxidase subunit 1 (cox1-5’) gene sequences]. Key diagnostic morphological characters for identification include relative thickness of the crust, assembly of erect filaments, number of chloroplast(s) and most importantly the organisation of reproductive structures. Results indicated that the common crustose brown algae in Malaysia and Lombok Island are species of Mesospora, Diplura and Neoralfsia expansa. Seven species of Mesospora were identified in the present study of which three were formally described (M. schmidtii, M. negrosensis and M. elongata) and four are putative new species to be described (Mesospora sp. C, Mesospora sp. D, Mesospora sp. 1 and Mesospora sp. 2). Partial output from this study leads to the recent description of Mesospora elongata Poong, Lim & Phang from Japan and Lombok Island and a new record of M. negrosensis for Malaysia. The presence of M. elongata in Malaysia is reported here for the first time since the initial publication of this taxon. iv Mesospora sp. C and M. schmidtii were reported earlier in Malaysia. This study also marks the first report of Mesospora sp. D (previously reported in Japan) and four putative species of Diplura for Malaysia and Indonesia. The taxon provisionally named “Mesospora” sp. 3 and the closely related Mesospora sp. G are likely members of a new genus. Other crustose brown algae examined in this study include a Ralfsia-like species and two yet-to-be identified taxa. The crustose brown algae are polyphyletic and occur in widely divergent clades among the brown algae with the majority placed in Ralfsiales while the rest are closely associated with other phaeophyceaen orders such as Sphacelariales and Ishigeales. Circumscription of Ralfsiales comprises the Ralfsiaceae, Neoralfsiaceae, Mesosporaceae and a possible new family to accommodate “Mesospora” sp. 3. Establishment of a new family for members of the genus Diplura is underway pending the collection of the generitype, Diplura simulans. Molecular analyses incorporating Hapalospongidion saxigenum indicate that Mesospora, currently synonymised with Hapalospongidion should be retained as a separate genus. The rbcL marker performed better in the elucidation of phylogeny at higher classification levels, whereas cox1-5’ is more suited as a barcoding marker for species level identification of the crustose brown algae.